2008
DOI: 10.1515/znc-2008-9-1023
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Attractant-Baited Trap for Oxythyrea funesta Poda (Coleoptera: Scarabaeidae, Cetoniinae)

Abstract: In electroantennographic tests isosafrol, methyl salicylate, (ð)-lavandulol, geraniol, (E)-anethol, and -ionone evoked the largest responses from antennae of female or male Oxythyrea funesta (Coleoptera: Scarabaeidae, Cetoniinae) adult beetles. In field trapping tests in Hungary the 1 : 1 blend of (ð)-lavandulol and 2-phenylethanol attracted significantly more adult O. funesta than the single compounds. The addition of (E)-anethol, a previously described attractant for the species, was without effect. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
1
18
0
3
Order By: Relevance
“…74 For example, cinnamyl alcohol and (E)-anethole, common flower scent components, attract Epicometis hirta (Scarabaeidae) (which damages the reproductive parts of flowers of several orchard trees and many ornamental bushes 75 ) and enhance the attractiveness of light blue color. 77,78 Constituents of plant volatiles change according to plant age and developmental stage, sometimes causing changes in the behavioral responses of the insects to the host plants. and Papaver spp., fruit trees such as Vitis spp., Prunus spp., Citrus spp., Malus spp., and various cereals.…”
Section: Feeding Attractants and Stimulantsmentioning
confidence: 99%
“…74 For example, cinnamyl alcohol and (E)-anethole, common flower scent components, attract Epicometis hirta (Scarabaeidae) (which damages the reproductive parts of flowers of several orchard trees and many ornamental bushes 75 ) and enhance the attractiveness of light blue color. 77,78 Constituents of plant volatiles change according to plant age and developmental stage, sometimes causing changes in the behavioral responses of the insects to the host plants. and Papaver spp., fruit trees such as Vitis spp., Prunus spp., Citrus spp., Malus spp., and various cereals.…”
Section: Feeding Attractants and Stimulantsmentioning
confidence: 99%
“…cuprea (trap codenamed 'BlueCetonia'; Vuts et al, 2010a) and E. hirta (trap codenamed 'BlueEpicometis'; Tóth et al, 2004;Schmera et al, 2004) were light blue (for reflectance spectrum, see Schmera et al, 2004) and differ with respect to the volatiles released (Table 1). In earlier field trials , a fluorescent yellow colour (for reflectance spectrum, see Jenser et al, 2010) resulted in higher catches of O. funesta than the yellow colour used earlier (reflectance spectra in Schmera et al, 2004), and was found to be efficient for the capture of O. funesta (Vuts et al, 2008). Consequently, this fluorescent yellow colour was used in Trials 1 and 2 in traps developed for catching O. funesta (termed 'FluorYellow').…”
Section: Field Trialsmentioning
confidence: 99%
“…Trial 3 ran from 28 May to 19 July and Trial 4 ran from 15 May to 21 July (number of blocks = 5, number of traps/site = 20). The treatments set up comprised: a combination of the colour plus the volatiles that gave high O. funesta catches [2‐phenylethanol : (±)‐lavandulol 1 : 1] (Vuts et al , 2008); the binary 2‐phenylethanol : (±)‐lavandulol blend without colour (transparent); colour without the binary blend; and transparent traps with no added colour and no volatiles.…”
mentioning
confidence: 99%
“…However, flowers of other families are visited less frequently. The species was included in the lists of harmful fauna as a pest of apple and peach orchards, vineyards, rosebush plantations, some vegetables and field crops in most countries of southern Europe feeding not only on pollen but damaging floral organs and even buds (Benfatto and Longo 1986;Milenkovic and Stanisavljevic 2003;Vuts, Imrei, and Tóth 2008;Ražov, Baric, and Dutto 2009;Stan, Tuca, and Mitrea 2009;Tuca, Mitrea, and Stan 2009;Ciancio and Mukerji 2010;Subchev et al 2012). Adults are quite conspicuous having a flat, rectangular-shaped, 8-12 mm long body, which is metallescent black in colour with a reddishgreenish shine.…”
Section: Introductionmentioning
confidence: 99%